2011
DOI: 10.1371/journal.pone.0028811
|View full text |Cite
|
Sign up to set email alerts
|

FHA-Mediated Cell-Substrate and Cell-Cell Adhesions Are Critical for Bordetella pertussis Biofilm Formation on Abiotic Surfaces and in the Mouse Nose and the Trachea

Abstract: Bordetella spp. form biofilms in the mouse nasopharynx, thereby providing a potential mechanism for establishing chronic infections in humans and animals. Filamentous hemagglutinin (FHA) is a major virulence factor of B. pertussis, the causative agent of the highly transmissible and infectious disease, pertussis. In this study, we dissected the role of FHA in the distinct biofilm developmental stages of B. pertussis on abiotic substrates and in the respiratory tract by employing a murine model of respiratory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 67 publications
(98 reference statements)
3
106
1
3
Order By: Relevance
“…Other potential mechanism for this phenotype are (i) the higher expression of FHA, Fim, and other adhesive factors in T44625 and (ii) the absence of the cyaA gene from T44625. We and others have previously shown that while FHA and Fim are required for Bordetella biofilm formation, the presence of cyaA is inhibitory (39,50,51). Interestingly, we did not observe enhanced expression of the bpsABCD genes encoding the Bps polysaccharide, a Bordetella surface polysaccharide critical for biofilm development (10,11).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Other potential mechanism for this phenotype are (i) the higher expression of FHA, Fim, and other adhesive factors in T44625 and (ii) the absence of the cyaA gene from T44625. We and others have previously shown that while FHA and Fim are required for Bordetella biofilm formation, the presence of cyaA is inhibitory (39,50,51). Interestingly, we did not observe enhanced expression of the bpsABCD genes encoding the Bps polysaccharide, a Bordetella surface polysaccharide critical for biofilm development (10,11).…”
Section: Discussioncontrasting
confidence: 67%
“…We have demonstrated that flagellar production early during biofilm formation followed subsequently by repression is required for robust biofilm formation and maturation (36). It has also been shown that FHA is required for efficient biofilm formation in both B. bronchiseptica and B. pertussis (50,51), and the presence of cyaA inhibits biofilm formation in B. bronchiseptica (51). Given the repression of flagellar genes, lower motility, upregulation of fhaB, and absence of cyaA in T44625, we hypothesized that T44625 will exhibit increased biofilm formation compared to RB50.…”
Section: Resultsmentioning
confidence: 88%
“…S1). FHA showing filamentous structure is also an important virulence factor in respiratory tract colonization, induction of biofilm formation and autoaggregation because it mediates inter-bacterial adhesion (Serra et al, 2011). Filaments similar to the short, straight filaments on the surface of wild-type bacteria like FHA also formed on the surface of (p)ppGpp-deficient mutant B. pertussis cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among the filaments on the surface of wild-type biofilms, the short and straight filaments had relatively uniform lengths (49.8±8.0 nm) that were very similar to the length of FHA filaments (Makhov et al, 1994). FHA is encoded by fhaB, and is a major mediator of cell-cell adhesion in B. pertussis (Menozzi et al, 1994;Serra et al, 2011). Therefore, fhaB transcript levels and FHA levels in wild-type cultures were compared with those in PMK21 cultures; fhaB transcript levels and FHA levels did not differ significantly between wild-type and mutant cultures (Table 3 and Fig.…”
Section: Morphology Of Biofilms Formed On Abiotic Surfaces By Wild-tymentioning
confidence: 96%
“…These proteins are similar to the LspA1 and LspA2 filamentous hemagglutinins from H. ducreyi (454), mutations of which have been shown to affect virulence (455). A similar filamentous hemagglutinin in Bordetella pertussis and B. bronchiseptica is required for biofilm formation and colonization of the nose and trachea in mice (456,457). FhaB2 in P. multocida has been implicated in virulence (70,458), and expression of FhaB2 was found to be reduced by 4-fold in a nonmucoid P. multocida variant, AL1114 (432).…”
Section: Survival In the Host Environmentmentioning
confidence: 99%